GRADE 10 STUDENTS' DIFFICULTIES IN CLASSIFYING LIVING THINGS USING DETERMINATION KEYS AT SMAN 1 RANTAU SELATAN - Sri Tami Ningsih Daulay; Hadni Rahma; Erlia Utami Panjaitan; Witma Novita Atnur; Rahmi Syafriyeti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Biology learning is often considered as a difficult material to understand by students, especially because of the many Latin terms and complex concepts. One of the challenging materials is Biodiversity, especially in determining the classification of living things using the determination key. This study aims to identify difficulties experienced by grade X students at SMAN 1 Rantau Selatan in using the determination key to classify living things. Based on the results of observations and interviews with teachers and students, it was found that students had difficulty in understanding the basic concepts of biodiversity, scientific terms, and how to use the determination key. Learning methods that are more theoretical and less involved in practical activities are the main factors causing this difficulty. Students want more field activities or direct observations that can help them understand the material more contextually. For this reason, this study suggests that biology learning involves more practical activities and direct observations of real objects and deepens students' understanding of scientific terms and Latin. With a more practical approach, it is hoped that students can more easily understand the material on biodiversity.